2018
DOI: 10.1007/jhep04(2018)014
|View full text |Cite
|
Sign up to set email alerts
|

How to succeed at holographic correlators without really trying

Abstract: We give a detailed account of the methods introduced in [1] to calculate holographic four-point correlators in IIB supergravity on AdS 5 × S 5 . Our approach relies entirely on general consistency conditions and maximal supersymmetry. We discuss two related methods, one in position space and the other in Mellin space. The position space method is based on the observation that the holographic four-point correlators of onehalf BPS single-trace operators can be written as finite sums of contact Witten diagrams. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
629
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(650 citation statements)
references
References 110 publications
20
629
0
1
Order By: Relevance
“…In particular, these works discussed the case where the light operator is a simple chiral primary operator (see (2.7)): [22] focussed on the case where the heavy state is made out of many copies of the same supergravity mode and found that the 4-point correlator at the gravity point matched precisely the orbifold theory result, suggesting that there is a non-renormalisation theorem for this type of correlators; [23] considered a more complicated heavy operator made out of two types of supergravity modes. This second case provides the first explicit example of a dynamical HHLL correlator, where the result in the SCFT strong coupling region is radically different from the one valid at 2 There is a vast literature on holographic four point correlators in the context of the AdS 5 /N = 4 SYM duality; see [18] for a detailed discussion of a modern approach to the problem and references to original papers. Here we focus on the AdS 3 /CFT 2 case and the HHLL correlators of which much less is known.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, these works discussed the case where the light operator is a simple chiral primary operator (see (2.7)): [22] focussed on the case where the heavy state is made out of many copies of the same supergravity mode and found that the 4-point correlator at the gravity point matched precisely the orbifold theory result, suggesting that there is a non-renormalisation theorem for this type of correlators; [23] considered a more complicated heavy operator made out of two types of supergravity modes. This second case provides the first explicit example of a dynamical HHLL correlator, where the result in the SCFT strong coupling region is radically different from the one valid at 2 There is a vast literature on holographic four point correlators in the context of the AdS 5 /N = 4 SYM duality; see [18] for a detailed discussion of a modern approach to the problem and references to original papers. Here we focus on the AdS 3 /CFT 2 case and the HHLL correlators of which much less is known.…”
Section: Introductionmentioning
confidence: 95%
“…From (3.22), and the known expressions for the subleading corrections to the conformal blocks, we can find the function S(v, u) order by order in v. Unfortunately we have not been able to find a closed form for it in position space, instead finding a closed form in Mellin space. We follow the conventions in [39], borrowing the language to describe holographic correlators. For a correlator of identical external operators of dimension ∆ ϕ , we define the Mellin amplitude M(s, t) by…”
Section: Mellin Amplitudementioning
confidence: 99%
“…13) Bulk reconstruction from large N bootstrap: There has been recent progress in building up AdS amplitudes from large N bootstrap, or bootstrap-inspired, methods. This is true both for "bottom-up" ingredients such as Witten diagrams [2,[20][21][22][23][24][25], and topdown, complete amplitudes in string/M-theory at both genus zero [26][27][28][29][30][31][32][33][34] and genus one [35][36][37][38][39][40][41][42][43]. It is natural to apply these insights to more abstract investigations of the AdS landscape.These topics invite many questions.…”
mentioning
confidence: 99%